Temporal distribution of the electrical energy on an exploding wire - Rodriguez Prieto, Gonzalo (2016)
An exploding wire system has been experimentally studied by the observation of its plasma dynamics and the electrical energy delivered by the supporting circuit to the metallic wire. Plasma radial expansion has been obtained from visible light streak images, meanwhile electrical energy transfer dynamics was derived from the analysis of voltage and current traces of the exploding wire circuit. In these measurements, a significant portion of the electrical energy has been transferred to the exploding wire circuit during the plasma expansion, and lower limits for the resistivity during the plasma expansion confirm the existence of a central liquid or solid metallic core in addition to the expanding plasma.